Multi-stakeholder perspectives on urban regeneration: a spatial gradient analysis of heat and pollution effects - Jingqi Zhang; Xinyue Gu (International Journal of Biometeorology, 2025)
The acceleration of urbanization has caused severe environmental problems for cities, making the implementation of sustainable urban regeneration projects an important part of urban construction. Previous studies have shown that different actions taken by various stakeholder groups at different stages of urban regeneration can affect the outcomes of urban regeneration. However, few studies have investigated the environmental impacts on the urban regeneration plots and their surroundings during the urban regeneration implementation stage under the leadership of different stakeholders. Therefore, this study selected 12 plots under three urban regeneration models—government-led, government-enterprise cooperation-led, and multi-stakeholder cooperation-led—and examined the median or mean values of land surface temperature, air temperature, carbon monoxide concentration, nitrogen dioxide concentration, and sulfur dioxide concentration for each season over four years, from pre-regeneration to the implementation stage. It analyzed the urban heat and pollution effects within the plots and in multiple ring buffer zones of 50 m, 150 m, and 350 m outside the plots. The results indicated that: (1) The land surface temperature within the plots was significantly influenced by urban regeneration, while the impact on air quality was not as noticeable; (2) During winter, the urban heat and pollution within the plots were least affected by the implementation of urban regeneration; (3) Urban regeneration models with government involvement as the leading party were more likely to mitigate the impact of urban regeneration project implementation on urban heat and pollution. These findings are of significant importance for furthering the sustainability of urban regeneration.